2018
DOI: 10.1111/jocn.14291
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of satisfaction and quality of life after immediate breast reconstruction using the BREAST‐Q©

Abstract: This study suggests the need for multidisciplinary attention during the first year of adjuvant treatment despite the benefits of immediate reconstruction. It shows the need for preoperative assessment of the level of nicotine dependence, anxiety and depression of smoking patients before preoperative counselling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
3
26
0
Order By: Relevance
“…Lastly, one study also found that patients who took anxiolytics also presented higher odds of having lower sexual well‐being after breast reconstruction.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Lastly, one study also found that patients who took anxiolytics also presented higher odds of having lower sexual well‐being after breast reconstruction.…”
Section: Resultsmentioning
confidence: 96%
“…Presence of lymphedema was identified as a significant predictor of lower physical well‐being on the chest, role function, cognitive function, and body image…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations